STIMULATION PROGRAM TO ENHANCE OPTIMAL DEVELOPMENT IN EARLY CHILDHOOD (CASE STUDY OF DEVELOPMENTAL ASSESSMENT OF 3-YEAR-OLD CHILDREN) - Anik Mukti Dwi Pangestu (Institut Agama Islam Negeri Palopo, 2025)
Parents have the primary responsibility for educating children, but in the new normal era, caregiving roles can be undertaken by other adults who are close to the child. The principles of child rearing are not confined to who performs them but are more focused on educational activities that stimulate child development. The importance of at least one strong relationship with a caring adult who pays attention to the child's well-being is crucial in achieving optimal development. WHO data indicates additional risks for children lacking consistent caregivers, with around 43% of children worldwide not reaching optimal development. In Indonesia, the prevalence of developmental deviations reaches 7.51%, and the goal of this program is to detect and address deviations early through a partnership between parents, the community, and healthcare professionals. Early detection involves regular and sustained analysis of the child's physical, psychological, and social aspects. In conclusion, stimulation programs have a positive impact on child development, and solutions involve continued stimulation at home, consulting with professionals, participating in stimulation groups, developing motor skills, focusing on creativity, open communication with educators, regular monitoring, and family support. This program helps children, such as FIR and AMS, overcome their developmental challenges, with positive outcomes in motor skills, focus duration, language, and social skills. Overall, these solutions support children's development towards their optimal potential.